Structural Performance of Reinforced Concrete Beams Incorporating Cathode-Ray Tube (CRT) Glass Waste - Jad Bawab; Jamal Khatib; Ali Jahami; Adel Elkordi; Elhem Ghorbel (Buildings, 2021)
The performance of reinforced concrete beams in the presence of cathode-ray tube (CRT) glass waste is examined. Four concrete mixes containing 0%, 10%, 20%, and 30% CRT glass waste as partial replacement of sand were prepared. The compressive and flexural strength as well as the modulus of elasticity of concrete were determined. Reinforced concrete beams with varying amounts of CRT glass were prepared and the three-point bending test was conducted. The load-deflection curve as well as the strain distribution along the depth of the beams were determined. Concrete containing CRT glass showed an increase in compressive strength, flexural strength, and modulus of elasticity especially at 10% replacement level. The load carrying capacity of reinforced concrete beam is higher when 10% of sand is replaced with CRT glass compared to the control beam and the beams with 20% and 30% CRT glass substitution. The failure mode of the reinforced concrete beams is flexural failure, and the failure pattern is similar for all beams. Strain distribution showed a better ductility at control beam where the deflection was higher than the other beams at the same load. Numerical analysis was conducted, and comparison was made with the experimental results. The comparison showed the accuracy of the software used, where the results of maximum load capacity and maximum deflection were very similar, and the difference did not exceed 5%. In addition, the tensile damage generated by the numerical analysis was very similar to that obtained by the experimental study.